Laser-Assisted Periodontal Management of Drug-Induced Gingival Overgrowth under General Anesthesia: A Viable Option - Tupili Muralikrishna; Butchibabu Kalakonda; Sumanth Gunupati; Pradeep Koppolu (Hindawi Limited, 2013)
Gingival overgrowth/hyperplasia can be attributed to several causes, but drug-induced gingival overgrowth/hyperplasia arises secondarily to prolonged use of antihypertensive drugs, anticonvulsants and immunosuppressants. The management is complex in nature considering the multitude of factors involved such as substitution of drug strict plaque control along with excision of the tissue to be performed under local anesthesia as outpatient. In the recent times, the patient's psychological fear of the treatment with the use of surgical blade and multiple visits has developed the concept of single visit treatment under general anesthesia incorporating a laser as viable option. The present case highlights the new method of management of gingival overgrowth.